Small-Bowel Obstruction CT Features with Plain Film and US correlations - Di Mizio, Roberto; Scaglione, Mariano (Springer Milan : Imprint: Springer, 2007)
Small bowel obstruction is a common but difficult clinical problem in terms of appropriate diagnosis and timely management. In clinical practice, radiologists play a key role in the assessment of small bowel obstruction and can guide physicians toward appropriate and timely management of the many indeterminate cases and situations. However, to understand and connect the pathophysiology to the imaging features remains the most difficult task radiologists face in their clinical activity. The aim of this book is connect pathophysiology to imaging using many illustrations and examples, emphasizing the capabilities and limitations of multidetector computed tomography and its role in the correct management approach to these disorders. Furthermore, the place of allied imaging modalities (plain film and ultrasound) in the clinical algorithm is comprehensively illustrated.